Clinical and Laboratory Characterization of Hemodialysis Patients in Relation to Survival Outcomes at a Tertiary Referral Hospital in Indonesia - Elisabeth Sipayung; I Wayan Nariata; Yassir; Rumaisah Satyawati; Surya Oto Wijaya; Gesang Setia Budi; Anitha; Rivaldiansyah; Siti Maemun; Aninda Dinar Widiantari (Current Internal Medicine Research and Practice Surabaya Journal)
Introduction: Despite advancements in hemodialysis care, disease progression and outcomes in adults with various comorbidities, particularly in Indonesia’s overburdened tertiary hospitals, remain poorly characterized, limiting tailored care strategies. This study analyzed clinical characteristics and laboratory parameters among hemodialysis patients at Sulianti Saroso Infectious Disease Hospital, Jakarta, Indonesia, with stratification by survival outcomes.